Influence of material nonlinearity on the durability of piezoelectric energy harvesters using macro fiber composite - Teoh, Lai Xing (2015)
Many researches and studies has been done to increase the output performance and bandwidth of Piezoelectric Energy Harvester (PEH). Yet, there are limited studies being done on the strength and durability aspects of piezoelectric materials such as Macro Fiber Composite (MFC). An energy harvester will still be deemed as impractical if it is to fail quickly even though it is able to produce high power output. This paper aims to study the nonlinearity and durability of MFCs. When they are subjected to both high and low excitation accelerations, conclusion could be drawn on how their performance varies and what are the kinds of behaviour and characteristic that can be expected. Experimental results showed that nonlinearity occurred even at low excitation acceleration which was unexpected. Also, MFC possess recovery properties where voltage output could potentially recover to a certain efficiency after MFC were deem to have failed. These two discoveries poses several implication on the strength and durability characteristic of the piezoelectric material which emphasize to take them into consideration when designing PEH for Wireless Senor Nodes (WSN). Durability test also suggest that low excitation acceleration produces consistent power output even after failure and recovery occurred. However, recovery process might take a considerable amount of time. PEH that was subjected to high excitation acceleration were significantly less stable and is discouraged for commercial purposes until more studies are made.